2005
DOI: 10.1590/s1519-69842005000100014
|View full text |Cite
|
Sign up to set email alerts
|

Body-size influence on defensive behavior of Amazonian moths: an ecophysiological approach

Abstract: Ectotherm locomotion is restricted by low temperatures, and many species, such as some flying insects, need to achieve thermal thresholds before taking off. Body size influences heat exchange between an animal and the environment. Therefore, larger animals have higher thermal inertia, and necessarily spend more time in pre-flight warming up, a critical period when they remain exposed and more susceptible to predators. Thus, one could expect larger animals, along their evolutionary history, to have developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In fact, previous studies showed that small workers of B. terrestris and B. lapidarius are faster and more agile than larger ones, for example at handling flowers of Cytisus scoparius (Stout, ). Similarly in lepidopterans, larger moths developed a more diverse repertoire of defensive behaviours, owing to physiological constrains of flight, in comparison with small moths (Oliveira, ). In a coleopteran ( Callosobruchus chinensis ), a positive correlation was observed between body size and death‐feigning duration, an alternative and rarer anti‐predator defence strategy (Hozumi & Miyatake, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, previous studies showed that small workers of B. terrestris and B. lapidarius are faster and more agile than larger ones, for example at handling flowers of Cytisus scoparius (Stout, ). Similarly in lepidopterans, larger moths developed a more diverse repertoire of defensive behaviours, owing to physiological constrains of flight, in comparison with small moths (Oliveira, ). In a coleopteran ( Callosobruchus chinensis ), a positive correlation was observed between body size and death‐feigning duration, an alternative and rarer anti‐predator defence strategy (Hozumi & Miyatake, ).…”
Section: Discussionmentioning
confidence: 99%
“…anti-predator behaviour, artificial spiders, Bombus terrestris, intraspecific variability, nectar availability, pollinator size are often exposed to various flower-dwelling predators (Dukas & Morse, 2003, 2005. In addition, they exhibit a high degree of intraspecific variation in body size (Goulson, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, various thermal constraints, as well as those related to flight physiology may be present in different species (e.g. Oliveira 2005). Additionally, we cannot ignore the phylogenetic constraints on body size, since, typically, closely related species of Lepidoptera appear to show only small differences in body size.…”
Section: Discussionmentioning
confidence: 99%
“…Ellsworth et al , 1989; Cavalieri & Kocak, 1995; Onstad & Gould, 1998; Small, 2007; Arthur, 2008; Tao et al , 2008a, b; Oppert et al , 2010), behavioral ecology (e.g. Oliveira, 2005; Lewis & Wedell, 2009; Ingleby et al , 2010; Lewis et al , 2011), the genetics and evolution of pheromone communication systems (e.g., Roelofs et al , 2002; Lassance, 2010; Fuji et al , 2011), parasitoid–host co‐evolution (e.g. Eliopoulos & Stathas, 2003; Roberts et al , 2006; Niogret et al , 2009), and physiology and development (e.g.…”
Section: Introductionmentioning
confidence: 99%